Highly purified transversely polarized optical needle generated by the hybridly polarized vector optical field with hyperbolic symmetry. (23rd September 2020) - Gao, Xu-Zhen; Zhao, Peng-Cheng; Sun, Xue-Feng; Yang, Fan; Pan, Yue; Li, Yongnan; Tu, Chenghou; Wang, Hui-Tian
Abstract: We design and generate a kind of hybridly polarized vector optical field (VOF) with hyperbolic symmetry for the first time. After tightly focusing the new VOF, an optical needle is achieved with sub-wavelength transverse size (∼ 0.3 λ 2 ), and the depth of focus (DOF) is about twice as large as the common optical fields such as linearly, circularly, radially and azimuthally polarized optical fields. Meanwhile, highly purified transversely polarized electric and magnetic needles can be achieved simultaneously, which is also superior to other VOFs. When inserting a binary phase mask with N concentric belts, ultra-long optical needles can be realized by tightly focusing the hybridly polarized VOF using the genetic algorithm. The DOFs are 4.68 λ, 5.95 λ, 10.01 λ, 12.16 λ and 14.41 λ when N = 2, 3, 4, 5 and 6, respectively. As the VOFs used in shaping optical needles were always limited to cylindrical VOFs in previous research, this kind of non-cylindrical VOF can provide a new choice in focal engineering. Moreover, the highly purified transversely polarized optical needles can be applied in various areas, especially in utilizing optical materials or instruments responsive to the transverse optical field only.